Incentives to corruption and inaction in the civil service: A mechanism design approach - Bugarin, Mauricio Soares; Meneguin, Fernando Boarato (Estudos Econômicos (São Paulo), 2016)
The present paper analyzes the institutional incentives public managers face in Brazil.A decision-theoretic model suggests that the constitutional principle of “Legality” induces tenured civil servants to adopt a non-innovative, bureaucratic management. On the other hand, temporary appointed managers tend to be more active, which could either generate higher social returns, in the case of socially inclined managers, or lower social return, in the case of managers involved in corrupt activities. A preliminary panel data econometric analysis spanning from 2002 to 2013 suggests that Ministries with higher percentages of temporary appointed managers tend to present higher levels of corruption. A mechanism design approach shows how institutions could be adjusted in order to stimulate socially-beneficial innovative management while curbing corrupt practices in the country.